Analisis SWOT UMKM Pengolahan Kelapa di Desa Gesikharjo Kecamatan Palang - Nisa, Nur Yahya Khairun (FEB Universitas Maritim Semarang, 2024)
The development of Micro, Small and Medium Enterprises (MSMEs) has a strategic role in improving community welfare, especially in rural areas. This research aims to analyze the strengths, weaknesses, opportunities and threats (SWOT) faced by coconut processing MSMEs in Gesikharjo Village, Palang District. Data was collected through in-depth interviews with MSME actors, field observations, and document analysis. The research results show that the main strengths of these MSMEs are the availability of local raw materials and community support. However, weaknesses such as technological and management limitations are still challenges. Opportunities such as increasing demand for processed coconut products in local and national markets provide bright prospects, although threats such as price competition and global market fluctuations still need to be watched out for. Research recommendations include strengthening the managerial capacity of MSME players, product innovation, and collaboration with the government and private sector to create a sustainable business ecosystem.